PENGARUH KOMPETENSI DAN PRODUKTIVITAS TERHADAP KINERJA OUTSOURCING PADA DEPARTEMENT ASSSETAND OFFICE MANAGEMENT PT. SEMEN BATURAJA (PERSERO) Tbk MELALUI MODERASI IKIM ORGANISASI - Mulyadi Oktovindo; Luis Marnisah; Fakhry Zamzam (Program Magister Manajemen Indo Global Mandiri University, 2020)
The purpose of this study was to determine the results of the analysis of Competency and Productivity Analysis of the Outsourcing Performance of the Asset and Office Management Department of PT. Semen Baturaja (Persero) Tbk. Through Organizational Climate Moderation, both partially and simultaneously in providing services to the management of PT. Semen Baturaja (Persero) Tbk. This study uses a quantitative verification method with a confirmative negative verification. The results of the analysis of the Competence of Organizational Iklmin prove positive and significant with a significance of 0,000 <0.05 and t arithmetic 6.422> t table 1.994, so that it can be attenuated against comparisons to organizations, Products towards organizational climate are proven by the results of data processing using SPSS version 23 significant and significant with t-test 7.115> t table 1, 994 and significance 0.000 <0.05. Based on the results of hypothesis testing using SPSS version 23, which contains positive and significant positive and significant joint-positive competencies and assessments of organizations with an F count of 30, 368> F table of 2,500 and a significance of 0,000 <0.05. 0,000 <0.05 and t count 9.036> t table 2.500 and a regression term of 0.739, so that this study succeeded in supporting empirical research in the field of research to improve performance. Then the conclusion of this study: a) outsourcing competencies that enjoy working in a team have a positive and significant effect in improving the performance of outsourcing where relationships are close and familiar. b) the level of outsourcing productivity supported by high morale, can significantly build outsourced fellow work that is familiar and mutually supportive in increasing production. c) Together competence and productivity influence in building a conducive organizational climate. The most influential research variable on organizational climate is productivity, then competency variable. d) passionate outsourcing competency when working in a solid team dam, will have a positive and significant impact on the performance of outsourcing helping each other in completing tasks so that the task load can be completed properly. e) productivity outsourcing in the development of asset and office management of PT. Semen Baturaja (Persero) Tbk, which has high morale, positively and significantly influences the improvement of outsourcing performance which always helps each other in completing tasks properly. f) the organizational climate built through outsourcing relationships is very close and familiar, significantly influencing the performance of outsourcing in the Department of Asset and Office Management of PT. Semen Baturaja (Persero) Tbk which always helps in completing tasks effectively. g) high outsourcing components, increased outsourcing productivity and a conducive organizational climate Department of Asset and Office Management PT. Semen Baturaja (Persero) Tbk, jointly influences the improvement of outsourcing performance which helps each other in completing tasks with optimal results.